Sourcebook for Evaluating Global and Regional Partnership Programs : Indicative Principles and Standards - Independent Evaluation Group (Washington, DC : World Bank, 2012)
At the March 30-31, 2006, meeting of the Organization for Economic Co-operation and Development (OECD)/Development Assistance Committee (DAC) network on development evaluation, representatives of the World Bank's Independent Evaluation Group (IEG) presented their observations on the growing need to develop consensus principles and standards for the evaluation of Global and Regional Partnership Programs (GRPPs), based on their recent reviews of a sample of such programs and their evaluations. The meeting was attended not only by members from the evaluation units of 23 bilateral agencies and development cooperation ministries, but also by representatives of the African Development Bank (AfDB), the Asian Development Bank (AsDB), the European Bank for Reconstruction and Development (EBRD), the Inter-American Development Bank (IDB), the International Finance Corporation (IFC), the International Monetary Fund (IMF), and the United Nations Development Program (UNDP). Participants at the meeting expressed broad support for the development of such principles and standards, and requested that IEG play a leading role in developing them. The present sourcebook of indicative principles and standards for evaluating GRPPs is the result of IEG response to this request. The purpose of the indicative principles and standards contained in this sourcebook is to improve the independence and quality of program-level evaluations of GRPPs in order to enhance the relevance and effectiveness of the programs.